Sagot :
Answer:
NUMBER:1
Simplifying
- 6 + 2y = 8
Solving
- 6 + 2y = 8
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-6' to each side of the equation.
- 6 + -6 + 2y = 8 + -6
Combine like terms: 6 + -6 = 0
- 0 + 2y = 8 + -6
- 2y = 8 + -6
Combine like terms: 8 + -6 = 2
- 2y = 2
Divide each side by '2'.
- y = 1
Simplifying
- y = 1
NUMBER:2
Simplifying
- 6 + 2u = 8
Solving
- 6 + 2u = 8
Solving for variable 'u'.
Move all terms containing u to the left, all other terms to the right.
Add '-6' to each side of the equation.
- 6 + -6 + 2u = 8 + -6
Combine like terms: 6 + -6 = 0
- 0 + 2u = 8 + -6
- 2u = 8 + -6
Combine like terms: 8 + -6 = 2
- 2u = 2
Divide each side by '2'.
- u = 1
Simplifying
- u = 1
Step-by-step explanation:
- CARRY ON LEARNING
- GOOD LUCK
- THANKS ME LATER
- BRAINLIES